Impact of Safe School Initiative Programme on Behaviour of Victims of Insurgency in Secondary Schools in North - East Nigeria - Chinwuba, Mary Adanna (MultiTech Publisher, 2024)
The purpose of this paper is to investigate the Impact of the Safe Schools Initiative programme on the behaviours of victims of insurgency in Secondary Schools in North-east, Nigeria. This study adopted a descriptive and Ex-post facto survey design. The population comprised Federal Government Colleges in Yobe, Taraba, Bauchi, Borno, Adamawa and Gombe State. A sample size of 365 was used. The instruments employed were a questionnaire and a check list. Respondents have the choice to select preferred option from the 4–point Agree to Disagree Likert scale. Descriptive and inferential statistics were employed in data analysis. The findings indicated that the safe school initiative programme impacted positively on the behaviours of victims of insurgency positively, the students no longer engage on secret activities during lessons hours nor hate teachers that corrects them. The result also revealed that the safe school initiative programme impacted positively the academic achievement of victims of insurgency. It also shows the Safe School Initiative Programme modified negative behaviours like drug addiction, fighting and cultism. Based on the findings, the paper hereby recommends that teachers should pay more attention to students in safe school initiative programme so that they could overcome the negative impact of insurgency on their academic achievement. They should prioritize their learning to be able to fit in with the level of learning of other regular students. Teachers should apply some psychological principles to mitigate the effects of the insurgency on the behavioural pattern of the students so that they could still feel a sense of belonging in the classroom.